Spatial variations in PM2.5 composition and source apportionment across six cities of Jiangxi, China: insights from the 2023–2024 new year haze episode - Wang, Qineng; Deng, Wei; Tu, Xiang; Wang, Jiao; He, Dan; Gong, Yuanjun; Tan, Zhaofeng; Lu, Keding (Frontiers in Environmental Science, 2025)
PM2.5 poses significant public health risks, with its sources and composition exhibiting pronounced spatial heterogeneity. While extensive research has focused on heavily polluted regions in northern China, the pollution structure of Jiangxi Province remains understudied. This study investigates the chemical composition and source apportionment of PM2.5 during a severe regional haze episode (25 December 2023–20 January 2024) across six cities in Jiangxi Province: Nanchang, Jiujiang, Pingxiang, Ji’an, Xinyu. Observed PM2.5 concentrations ranged from 44.1 to 76.6 μg/m3, dominated by water-soluble ions, organic matter (OM), and carbonaceous aerosols. Spatial analysis revealed a pollution hotspot centered on Nanchang and Jiujiang, characterized by distinct gradients in SNA (SO42−, NO3−, NH4+) and OM. Based on local emission patterns and topographic features and the component concentration differences of PM2.5, we speculate that there are three regional patterns: (1) Northern cities, characterized by high loadings of NO3− (industrial), OM (VOCs-derived), and SO42− (promoted by lake air masses with high humidity); (2) Central cities, dominated by local agricultural NH4+ and conversion from industrial gaseous sources precursors enhanced by local photochemistry; (3) Southern Jiangxi, where vehicular NOx-to-NO3− conversion predominated, exacerbated by topographic stagnation from the Nanling Mountains. Positive Matrix Factorization (PMF) resolved city-specific sources: secondary formation and combustion in Nanchang; industrial and vehicular emissions in Jiujiang; agricultural NH4+ and traffic in Pingxiang; mixed industrial-traffic sources in Ji’an; and vehicle-derived NO3− with dust in Ganzhou. These findings underscore spatiotemporal heterogeneity in energy structures and regional transport pathways, providing a scientific basis for region-specific PM2.5 control strategies in Jiangxi Province, China.